Review of the genus Cilliba von Heyden (Acari: Uropodina: Cillibidae) - Stachowiak, Marcin; Halliday, Bruce; Bɫoszyk, Jerzy (Zootaxa, 2008)
We review the systematics, biogeography, ecology, and phylogeny of the genus Cilliba von Heyden (Acari: Uropodina: Cillibidae). The genus includes eight species, all from Europe. Keys are provided for identification of the females, males, and deutonymphs. Re-descriptions are given for C. athiasae (Hirschmann & Zirngiebl-Nicol), C. cassidoidea (Hirschmann & Zirngiebl-Nicol), C. erlangensis (Hirschmann & Zirngiebl-Nicol), C. sellnicki (Hirschmann & ZirngieblNicol) and C. stammeri (Hirschmann & Zirngiebl-Nicol). The only other genus in the family Cillibidae is Australocilliba Athias-Binche & B»oszyk, which occurs in Australia and South America. Most species of Cilliba are bisexual and probably arrhenotokous, but C. erlangensis and C. rafalskii B»oszyk et al. appear to be thelytokous.